Solving the revenue reconciliation problem of distribution network providers using long-term marginal prices - Maria Teresa Ponce de Leão (2003)
In this paper we describe an integrated methodology to compute Long Term Marginal Prices in distribution networks. Long Term Marginal Prices are considered the most interesting and economically sound way of allocating network costs to users. Additionally, they inherently deal with the Revenue Reconciliation Problem, as they generally do not require other large supplementary tariff terms. The proposed methodology uses Fuzzy Sets to model uncertainties in load forecasts and considers several criteria to guide the identification of solutions. At the end, there is a final decision-making step to select the most adequate expansion plan according to the preferences of the Decision Maker.